A Study On The Relationship Between Exhibition Experience And Behavioral Intention, And The Mediating Effect Of Satisfaction And Brand Assets In Corporate Promotion Exhibition Halls - Seung-Wan, Ju (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Currently, Korean companies operate corporate promotion halls, memorial halls and museums, centering on large corporations, making them a place for long-term communication beyond the short-term contact with consumers. In addition, companies have provided recently virtual exhibition experiences through the homepage or apps to the corporate publicity exhibition halls, which are operated by the company, and are being developed in parallel with the existing exhibition experiences. Therefore, this study conducted an empirical analysis to find out the effect of the exhibit experience of the corporate publicity exhibition hall on the consumer behavioral intention with the subject of the visitors who have experienced the exhibition experience of the domestic corporate publicity exhibition hall. Followings are the implications for the results. First, the corporate publicity exhibition hall did not have a specific effect on the behavioral intention of customers simply by exhibiting and viewing. This indicates that companies that operate or prepare to open the corporate publicity exhibition hall should avoid such simple experiences or simple viewing facilities. Second, the corporate publicity exhibition hall cannot induce customers' behavior simply by exhibiting experiences. The results will be more efficient when the corporate publicity exhibition hall is operated in combination with the brand assets of the company presented in this study or tangible and intangible assets of other companies. Third, as derived from the results of the study, corporate product brands are boldly exposed to consumers and very sensitive to consumers, affecting their behavioral intentions. The positive image of a product brand will lead to satisfaction and behavioral intentions, which in turn will affect the company's sales growth. Therefore companies should be very careful in managing their product brand. The academic significance of this study is in that it investigated the relationship between satisfaction, brand assets, and behavioral intention through the exhibition experience in the corporate publicity exhibition hall by conducting empirical analysis of the relationship systematically. In addition, it is expected to be used as a practical basic material that can be more practical in producing exhibition experiences when newly opening a corporate publicity exhibition hall or remodeling an existing corporate publicity exhibition hall. In the follow-up study, in order to provide the best exhibition experience to visitors to a company publicity exhibition hall, various variables such as human and material elements of the company publicity exhibition hall, such as how to guide at an information desk, the contact point with customers as well as four elements of experience. In addition, it will have its own meaning if research is conducted on local small and medium-sized businesses in addition to the corporate publicity exhibition hall centered on large companies.